Metabolic-Nutritional Associations with Depression in Elderly Chronic Kidney Disease Patients: Hemodialysis Versus Non-Dialysis Populations - Cakici, AE; Bilir, I; Ozdemir, S (My University)
Background/Objectives: This study aimed to evaluate the interrelationship between depression and nutritional-metabolic status in geriatric patients with chronic kidney disease (CKD), and to identify the contributing clinical and sociodemographic factors, with a particular focus on differences between patients receiving and not receiving hemodialysis treatment. Methods: This cross-sectional descriptive study was conducted between September 2023 and September 2024 in Gaziantep, Turkey. A total of 152 CKD patients aged 65 years and older were included, with 78 receiving hemodialysis and 74 managed without dialysis. Nutritional status was assessed using the Mini Nutritional Assessment-Short Form (MNA-SF), and depression levels were measured using the Geriatric Depression Scale-Short Form (GDS-SF). Laboratory parameters such as hemoglobin and serum albumin were also recorded. Results: A total of 152 geriatric CKD patients were included, with 78 (51.3%) undergoing hemodialysis and 74 (48.7%) not receiving dialysis. The non-dialysis group had significantly higher age (77.07 +/- 8.61 vs. 70.13 +/- 7.76 years, p = 0.001) and BMI (28.44 +/- 4.70 vs. 25.18 +/- 4.75, p = 0.001). Serum albumin levels were lower in non-dialysis patients (2.53 +/- 0.67 vs. 3.50 +/- 0.465 g/dL, p < 0.001), while hemoglobin (12.44 +/- 2.03 vs. 11.16 +/- 1.92 g/dL, p = 0.001) and ALT levels (17.16 +/- 13.06 vs. 8.53 +/- 4.31 U/L, p = 0.001) were higher. Malnutrition was more frequent among non-dialysis patients (20.3% vs. 9.0%, p = 0.033). Although depression was more common in this group, the difference was not statistically significant (p = 0.091). A moderate negative correlation was observed between MNA-SF and GDS-SF scores (r = -0.426, p < 0.01). Serum albumin positively correlated with MNA-SF (r = 0.374, p < 0.01) and negatively with GDS-SF (r = -0.323, p < 0.01). Conclusions: Malnutrition was more frequent among elderly CKD patients not receiving hemodialysis, whereas depression prevalence did not differ significantly between groups. A significant correlation between nutritional status (MNA-SF, serum albumin) and depressive symptoms (GDS-SF) was observed in the overall CKD cohort, underscoring the close interplay between metabolic and psychological health in this population. These results highlight the need for routine screening and integrated management of both nutrition and mental health in elderly CKD patients, and future longitudinal studies are warranted to determine causal pathways and predictive value.
Keywords: chronic kidney disease; geriatric nephrology; hemodialysis; depression; nutritional status; integrated care; quality of life